Neuroplasticity of peripheral axonal properties after ischemic stroke - Hung-Ju Chen; Jowy Tani; Cindy Shin-Yi Lin; Tsui-San Chang; Yi-Chen Lin; Ting-Wei Hsu; Jia-Ying Sung (PLoS ONE, 2022)
Objective This study investigated how peripheral axonal excitability changes in ischemic stroke patients with hemiparesis or hemiplegia, reflecting the plasticity of motor axons due to corticospinal tract alterations along the poststroke stage. Methods Each subject received a clinical evaluation, nerve conduction study, and nerve excitability test. Nerve excitability tests were performed on motor median nerves in paretic and non-paretic limbs in the acute stage of stroke. Control nerve excitability test data were obtained from age-matched control subjects. Some patients underwent excitability examinations several times in subacute or chronic stages. Results A total of thirty patients with acute ischemic stroke were enrolled. Eight patients were excluded due to severe entrapment neuropathy in the median nerve. The threshold current for 50% compound muscle action potential (CMAP) was higher in paretic limbs than in control subjects. Furthermore, in the cohort with severe patients (muscle power ≤ 3/5 in affected hands), increased threshold current for 50% CMAP and reduced subexcitability were noted in affected limbs than in unaffected limbs. In addition, in the subsequent study of those severe patients, threshold electrotonus increased in the hyperpolarization direction: TEh (100–109 ms), and the minimum I/V slope decreased. The above findings suggest the less excitable and less accommodation in lower motor axons in the paretic limb caused by ischemic stroke. Conclusion Upper motor neuron injury after stroke can alter nerve excitability in lower motor neurons, and the changes are more obvious in severely paretic limbs. The accommodative changes of axons progress from the subacute to the chronic stage after stroke. Further investigation is necessary to explore the downstream effects of an upper motor neuron insult in the peripheral nerve system.